Presentation of the book The Cathedral of Ayaviri in time. Historical and artistic study of the church of San Francisco de Ayaviri from the 16th century to the present - Samanez, Roberto (2011)
Presentation of the book The Cathedral of Ayaviri in time. Historical and artistic study of the church of San Francisco de Ayaviri from the 16th century to the present, written by Carlos Zegarra Moretti.